Analisis Pengaruh Multiplayer services terhadap Daya Tarik Game MOBA - Tofent Tofent; Hendi Sama (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Video Games have evolved rapidly over the last few decades and come in a variety of genres. MOBA or Multiplayer Online Battle Arena is one of them, this genre is known for its multiplayer and competitive scene. This study aims to analyze if MMO or Massively Multiplayer Online affects player’s interest in playing MOBA games using multi-method to gather a consensus of respondents. DeLone & McLean is the model used in this study. The findings in this study show that people are interested in MOBA games because of the visual and gameplay of MOBA itself, While MOBA games do not affected by player’s interest in MMO or multiplayer services’ variable.